2003
DOI: 10.1002/cncr.11373
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis in long‐term survivors after allogeneic or autologous stem cell transplantation

Abstract: Since components of the Japanese diet that might be responsible for the relatively low breast cancer incidence rates observed in Japan have not been clarified in detail, a case‐referent study with reference to menopausal status was conducted using data from the hospital‐based epidemiologic research program at Aichi Cancer Center (HERPACC). In total, 2,385 breast cancer cases were included, and 19,013 women, confirmed as free of cancer, were recruited as the reference group. Odds ratios (ORs) and 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
2
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 60 publications
(42 reference statements)
1
65
2
2
Order By: Relevance
“…40 The positive effects on osteoblasts may be particularly important in allo-transplanted patients, since previous evidence indicated a persistently reduced regenerative and functional capacity of osteoblast precursors. 3,23,24,41,42 Although we did not evaluate osteoblastic lineage behavior in patients treated by risedronate, it is likely that BMD improvement produced by risedronate is at least in part related to its anabolic effects, in analogy with what we documented with zoledronic acid. 13 As a matter of fact, the improvement observed in the patients treated by bisphosphonates was highly significant at both LS and FN.…”
Section: Discussionmentioning
confidence: 96%
“…40 The positive effects on osteoblasts may be particularly important in allo-transplanted patients, since previous evidence indicated a persistently reduced regenerative and functional capacity of osteoblast precursors. 3,23,24,41,42 Although we did not evaluate osteoblastic lineage behavior in patients treated by risedronate, it is likely that BMD improvement produced by risedronate is at least in part related to its anabolic effects, in analogy with what we documented with zoledronic acid. 13 As a matter of fact, the improvement observed in the patients treated by bisphosphonates was highly significant at both LS and FN.…”
Section: Discussionmentioning
confidence: 96%
“…An 'early BMD loss phase' that commences with antineoplastic therapy before transplant typically lasting up to the first 3 to 5 years, followed by a 'later BMD recovery phase' in which recovery occurs from accumulated insults once GvHD and subclinical inflammation subside. [20][21][22] The 'early BMDL phase' is dramatic; Yao et al 23 have shown that BMDL between baseline and day 100 DEXA scans is equivalent to 7-10 years of aging of bones for autologous and 13-17 years for allogeneic SCT recipients. Factors influencing the 'early BMD loss phase' include the intensity of antineoplastic therapy, conditioning, GvHD, immunosuppression and cumulative steroid exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Factors influencing the 'early BMD loss phase' include the intensity of antineoplastic therapy, conditioning, GvHD, immunosuppression and cumulative steroid exposure. [20][21][22] Management principles in the 'early BMD loss phase' include reducing exposure to corticosteroids, probably the strongest modifiable risk factor, and fracture risk returns to baseline 6-18 months after discontinuing corticosteroid exposure. 24 Calcium and vitamin D supplementation alone in the 'early BMDL phase' are unable to prevent BMDL 9,25,26 but probably play a critical role in the 'later BMD recovery phase'.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that cumulative intravenous methylprednisolone at doses of >2 g for >3 months significantly increased the risk for ON [16]. The frequent inclusion of corticosteroids in treatment protocols for various medical conditions, such as acute lymphoblastic leukemia (ALL), various lymphomas, and either solid organ or bone marrow transplantation, clearly put these patients at an increased risk for ON [17][18][19][20][21][22][23][24]. In a prospective MRI study, the incidence of ON associated with corticosteroid therapy was significantly higher in systemic lupus erythematosus (SLE) patients than in non-SLE patients (37 versus 21 %, P=0.001) [25•].…”
Section: Corticosteroidsmentioning
confidence: 99%